Beyond magenta transgender teens speak out - Kuklin, Susan (Candlewick Press, 2014)
"Author and photographer Susan Kuklin met and interviewed six transgender or gender-neutral young adults and used her considerable skills to represent them thoughtfully and respectfully before, during, and after their personal acknowledgment of gender preference. Portraits, family photographs, and candid images grace the pages, augmenting the emotional and physical journey each youth has taken. Each honest discussion and disclosure, whether joyful or heartbreaking, is completely different from the other because of family dynamics, living situations, gender, and the transition these teens make in recognition of their true selves."--Amazon.com, viewed February 12, 2014.